Smartphone and privacy concerns: Not so smart - Matias, Filipa da Silva (2019)
Smartphone is one of the most important information technology devices, so people feel the desire to adapt to it in order to keep up with technological developments (Lee, Chang, Lin & Cheng, 2014). Although recent studies have attempted to unravel the behavioral intentions to use smartphones (e.g. Bruner & Kumar, 2005; Liu & Yu, 2017) by analyzing different factors, there is a gap in the axiological dimension of this decision process (Chun, Lee & Kim, 2012). Privacy concern is one of the most relevant issues (Pew Research Center, 2014) and, consequently, this study is set to test in which measure privacy, as an axiological expression, override the hedonic factors associated with the behavioral intention of using smartphones. With a sample of 211 smartphone users we tested in which measure the importance given to privacy acts as a moderator variable in a model that comprehens ease of use, usefulness, and fun as predictors of behavioral intention to use smartphones. Findings show privacy is a key-driver in the behavioral intention of using smartphone, with particular emphasis health-related apps.